Faktor-Faktor Yang Mempengaruhi Return Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Pradrwati, Henny Damayanti (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to obtain empirical evidence about the factors that influence stock return in the manufacturing companies that listed in Indonesia Stock Exchange. Independent variables used in this research are price to book value, return on equity, return on asset, earnings per share, and current ratio. The populations used in this study are manufacturing companies listed in Indonesia Stock Exchange during 2013-2016. The sample of this research use 50 manufacturing companies. Samples are obtained through purposive sampling method. Data are analyzed using multiple regression analysis. The results shows that price to book value, return on equity, return on asset, and earnings per share have influence towards stock return. However, current ratio have no influence toward stock return.